The violated democracy - Bobbio, Norberto (2017)
Among all the criminal actions that men can carry out against other men, an attack is one of those that comes closest to radical evil: it is the ultimate crime, murder, consciously directed against the innocent. He who places a lethal bomb on a train or in a station waiting room knows with certainty that the victims his gesture produces have, in relation to the end or ends he proposes, no guilt. It does not hit the enemy, real or presumed, but on a whim those who happen to find themselves on that train, or in that waiting room, in that square. I don’t mean to say that the terrorist doesn’t have an enemy to target or take revenge on. But his enemy is elsewhere: the slaughter of the innocent is just a means to indirectly target an enemy that only he knows or should know who he is and where he is. Perhaps there is no more perverse way to reduce man to a means than to consider his violent death as a pure means of an unknown design. [...]